Preaching and Teaching Sound Doctrine Based on Christocentric Doctrine by Church Leaders for the Transformation of Church Members - Samuil-Ashton Satu (Angelion, 2020)
AbstractPreaching and teaching sound doctrine based on Christocentric doctrine is of utmost importance to Christian belief, as it is the cornerstone of the New Testament, the Holy Trinity (the Father, the Son , and the Holy Spirit), and the Apostles. So we will not do less as Christians. The purpose of a sermon is to bring about holy transformation through the Word of God in the life of the listener. The preachers need to help the audience put the Word into their lives. With respect to this, Bryan Chapell notes that “without application, a preacher has no reason to preach.” Thus he proposed five questions for the application for Christocentric doctrinal preaching, which should first be addressed to the preachers themselves. Through these questions, preachers can help to change the life of congregation by applying Christocentric doctrinal preaching. Furthermore, evidence of transformation within believers is seen in the way that the likeness and glory of Christ is increasingly reflected (2 Corinthians 3:18). The apostle Paul said, “You, however, are controlled not by the sinful nature but by the Spirit, if the Spirit of God lives in you. And if anyone does not have the Spirit of Christ, he does not belong to Christ” (Romans 8:9). Believers must be led by the Spirit of God to be considered as children of God. And it is by the power of the Spirit of God that Christ is living within them. The life transformed reflects Apostle Paul's thoughts in Galatians: “I have been crucified with Christ and I no longer live, but Christ lives in me. The life I live in the body, I live by faith in the Son of God, who loved me and gave himself for me” (Galatians 2:20). Conversely, if the church leaders ignore Christocentric doctrinal preaching and the application of the Word of God in the church members’ lives, then the transformation of the  believers’ lives will be thwarted. This study uses descriptive and phenomenological analysis of the data collected to find out why there is no change in some christians life-style and values. The results of this analysis will give impetus to revitalise the church to have a healthy theology for a healthy church of transformed lives in Christ Jesus.AbstrakBerkhotbah dan mengajar doktrin yang sehat berdasarkan dokrin Kristosentrik adalah terpenting dalam kepercayaan Kristen karena itulah penegasan Perjanjian Baru, Allah Trinitas (Allah Bapa, Allah Anak dan Allah Roh Kudus) dan Rasul-Rasul. Karena itu, seorang Kristen harus juga berbuat demikian. Tujuan dari khotbah ialah transformasi hidup melalui pendengaran Firman Allah. Pengkhotbah harus membantu jemaat mengapplikasikan Firman Allah dalam hidup mereka. Bryan Chapell menyatakan, “Tanpa aplikasi, seseorang pengkhotbah itu langsung tidak punya alasan untuk berkhotbah”. Dengan itu, ia menyarankan lima hal untuk penerapan atau applikasi kepada pengkhotbah terlebih dahulu. Melalui pertanyaan ini, pengkhotbah bisa membantu kehidupan jemaat untuk diubah dengan penerapan Fiman Allah berbasiskan doktrin Kristosentrik. Selain itu, bukti transformasi dalam hidup seseorang Kristen dilihat bagaimana seseorang itu kian mencerminkan gambar dan kemuliaan Kristus (2 Korintus 3:18). Rasul Paulus menyatakan, “Tetapi kamu tidak hidup dalam daging, melainkan dalam Roh, jika memang Roh Allah diam di dalam kamu. Tetapi jika orang tidak memiliki Roh Kristus, ia bukan milik Kristus” (Roma 8:9). Untuk dianggap sebagai anak-anak Tuhan,orang percaya harus dipimpin oleh Roh Allah. Dan melalui kuasa Roh Kudus, Kristus diam di dalam mereka. Hidup transformasi mencerminkan pemikiran Rasul Paulus dalam Galatia : “Namun aku hidup, tetapi bukan lagi aku sendiri yang hidup, melainkan Kristus yang hidup di dalam aku. Dan hidupku yang kuhidup sekarang di dalam daging, adalah hidup oleh iman dalam Anak Allah yang telah mengasihi aku dan menyerahkan diri-Nya untuk aku.” (Galatia 2:20). Sebaliknya, jika pemimpin gereja mengabaikan khotbah doktrin Kristosentrik dan applikasi Firman Allah dalam kehidupan jemaat, maka transformasi kehidupan jemaat akan digagalkan. Penelitian ini menggunakan kaedah deskriptif dan fenomenologi analisis atas data-data yang dikumpulkan untuk menemukan jawapan mengapa kehidupan dan cara hidup banyak jemaat tidak berubah. Hasil analisa ini akan memberi dorongan kepada gereja untuk memperoleh teologi yang sehat untuk membangun gereja yang sehat yang hidup dalam Kristus Yesus.